Variability in the Duration and Thoroughness of Hand Hygiene. (13th September 2019) - Mumma, Joel M; Durso, Francis T; Casanova, Lisa M; Erukunuakpor, Kimberly; Kraft, Colleen S; Ray, Susan M; Shane, Andi L; Walsh, Victoria L; Shah, Puja Y; Zimring, Craig; DuBose, Jennifer; Jacob, Jesse T
Abstract: We observed 354 hand hygiene instances across 41 healthcare workers doffing personal protective equipment at 4 hospital-based biocontainment units. We measured the duration and thoroughness of each hand hygiene instance. Both parameters varied substantially, with systematic differences between hospitals and differences between healthcare workers accounting for much of the variance. Abstract : Using observations of hand hygiene practices during simulated patient care in biocontainment units, we partitioned variance in the duration and thoroughness of hand hygiene into that attributable to differences between facilities and differences between healthcare workers.